Healing with sound: exploring possible applications of Qur’anic recitation in cell culture - Hashim, Rosyafirah; Sha'ban, Munirah; Zainuddin, Zainul Ibrahim (IIUM Press, 2017)
There are evidences of research done in relation to sound healing in dealing with various health problems. Brain, auditory cells and other cells in the human body have been shown to react to sound. The use of Qur’anic recitation for therapeutic purposes can be traced back to the times of Prophet Muhammad (s. a. w.). Listening to the Qur’anic recitation can have therapeutic effects even on individuals who do not understand the meaning of the verses. However, there is little to suggest the effect of Qur’anic recitation on cell cultures. The Scopus database was examined for scientific writings that involve the effect of sound, with higher emphasis on “Healing with Qur’anic recitation”. The positive effects of sound identified from the literatures support future studies to examine the effects of Qur’anic recitation on cell cultures. However, this paper adopted a cautious approach to associating Qur’anic recitation to sound healing.